Endangered Food Systems: Agriculture, Nutrition and Cultural Heritage in Bali, Indonesia - Reuter, Thomas A. (Unisia, 2022)
The long-established, traditional food systems maintained by indigenous and local communities in developing countries have witnessed rapid changes in production, trade, and consumption patterns in recent decades. These changes tend to be detrimental to ecological and human health. The central highlands and northeastern coast of the island of Bali, Indonesia, are illustrative examples of such a regional food system, with centuries of documented history and subject to a longitudinal ethnographic study by the author. This paper describes the recent decline in local biodiversity, ecological sustainability, social resilience, nutrition, and food security in this food system in the wake of agricultural ‘modernization.’ Greater attention to the culturally modulated dimensions of food systems, it is argued, will contribute to creating a rural development model for (re-)creating moral economies that support ecologically and socially responsible food systems.